A low-cost passenger safety protection system based on laser ranging. Issue 1 (August 2021) - Wang, Fuhao; Wang, Hongbo; Zhang, Xueze; Dong, Yu; Lai, Zhiping; Wang, Jiawei
Abstract: In 2021, the total number of motor vehicles in China has exceeded 370 million. In the process of getting off the car, avoiding accidents between passengers and non-motor vehicles is of great significance for reducing casualties and economic losses. Therefore, this paper designs a low-cost passenger safety protection system based on laser ranging. Following the principle of easy integration and miniaturization, the hardware design and software design of the system have been completed. The mathematical model of arrival time-distance of non-motor vehicle under various speeds is established. Laser-ranging data is used to build the map, and the map can be used for non-motor vehicle identification and speed estimation. The function and precision of the system are tested. The experimental results show that 1) the established model can automatically determine whether passengers can get off the car safely and close the door in dangerous situations; 2) the mapping method based on laser ranging can effectively distinguish between non-motorized vehicles and roadsides. The accuracy of non-motor vehicle speed measurement is about 90%. The designed passenger safety protection system has high practicability.